Cost-effectiveness of postpartum haemorrhage first response bundle and non-surgical interventions for refractory postpartum haemorrhage in India: an ex-ante modelling study - S Resch, PhD; M Guha, MPH; Z Ward, MPH; S Suarez Zarate, MD; A Borovac-Pinheiro, MD; M Omotayo, PhD; L Garg, MD; S Hansel, MPH; T Burke, MD (Elsevier, 2020)
Background: Postpartum haemorrhage (PPH) is the leading cause of maternal mortality worldwide and India accounts for approximately 19% of global maternal deaths, with PPH as the leading cause. In recent years, care bundles have been shown to increase adherence to clinical guidelines and improve patient outcomes. The objective of this study was to develop a PPH cost-effectiveness model to estimate the potential health impact and cost-effectiveness of a quality improvement programme for PPH management featuring a first response bundle and a set of refractory PPH interventions in health facilities in Uttar Pradesh, India. Methods: We used a decision tree model to compare the status quo delivery of PPH care in Uttar Pradesh with two scenarios in which recommended bundles for PPH management were optimally applied. Status quo PPH care includes intravenous fluids, uterotonics, and uterine massage delivered with a setting-specific probability that increases with the level of health facility. In the strengthened PPH care scenario, status quo interventions are combined with tranexamic acid in a first response bundle which is used in all PPH cases, plus manual placenta removal and suturing when indicated. In the enhanced PPH care scenario, PPH care is further enhanced through implementation of non-surgical interventions for managing refractory PPH (including uterine balloon tamponade, aortic compression, and non-pneumatic anti-shock garment). For each scenario, we conducted a Monte Carlo simulation of cohorts of 1 million women delivering at home, subcentres, primary-health clinics, community-health centres, and district hospitals. The results were scaled to represent the annual number of deliveries in Uttar Pradesh and their distribution across health facilities. The main outcomes were PPH cases, PPH deaths, and PPH surgical procedures. Findings: Compared with status quo, perfect implementation of enhanced PPH care was predicted to reduce PPH-related maternal mortality in intervention facilities by 98%, from 10·7 to 0·3 per 100 000 deliveries, averting 450 deaths per year in Uttar Pradesh. Although enhanced PPH care would increase annual costs associated with the active management of the third stage of labour and non-surgical PPH management by US$190 000 and $300 000, respectively, service delivery costs were reduced by $1·42 million per year. Strengthened PPH care was predicted to prevent PPH deaths and reduce service delivery costs compared with status quo, but to have only 66% of the health impact and 63% of the cost-savings compared with enhanced PPH care. The upfront programme implementation costs and persistence of change in PPH management after implementation are uncertain. If enhanced PPH care were implemented with up to $2300 per facility, and the change in PPH management persisted for at least 2 years, the programme is estimated to be cost-effective (<0·5 GDP per capita per life year gained). Interpretation: Implementation of an enhanced PPH care programme, including the first response bundle and non-surgical refractory PPH interventions, is likely to be cost-effective and life-saving in Uttar Pradesh, India. Moreover, enhanced PPH care is likely to generate more health impact and cost-savings compared with strengthened PPH care because of the greater reduction in number of surgeries needed. Funding: Bill & Melinda Gates Foundation